PENDEKATAN SOSIOLOGIS DALAM STUDI ISLAM DAN KONTEKSTUALISASI PADA TRANSAKSI KEUANGAN SYARIAH - Apri Suhartanto (DAS Institute, 2021)
The development of religious understanding in a community should be a positive one and provide benefits. The sociological approach in practice can be one solution in understanding the texts of the Koran and texts from secondary sources, namely hadith. This study aims to provide an overview of how the contextualization of the texts of the Qur'an and Hadith in social life. Especially the practice of transactions that are often carried out at Islamic Financial Institutions